Hány szlovák nemzetiségű gyógyszerész élt a tatárjárás idején Magyarországon? : adalékok Bibó István Közép-Európa képéhez - Kupa, László (Közép-Európai Közlemények, 2013)
István Bibó (1911–1979) has not written monograph on Central Europe, but he examined the history of this area in several significant studies. He has drawn attention already at the end of the Second World War, to the serious social, political problems of the area, including those pathological symptoms, which –according to Bibó –have led to both of the World Wars. (Bibó’s research regarding Central Europe expanded into Germany, Czechoslovakia, Hungary and Poland)Examining the history of Europe approximately from the Middle Age, a number of elements, even if only in fragments, was existed also in Central Europe, of the ‘freedom programme’ sketched out by Bibó. The ethnical conflicts of the region were heightening from the 18th century, and then turned into historical traumas, and political hysteria of the twentieth century. Bibó considered the Trianon Peace Treaty such a trauma, therefore he rejected and he raised his voice against the infringements of Hungarian minorities by Czechoslovakians and Romanians. The resolving of the ethnic conflicts Bibó proposed the consistent application of the principle of self-governance and the introduction of political arbitration, but in ‘long term’ he trusted in the reconciliation of these nations. In his view such a historic turn can bring positive change also for the Hungarian minorities of Hungary’s disannexed territories. Key words: Bibó István; self-governance; legal aspects of ethnic conflict; minority autonomy; minority rights/human rights; political arbitration.